2023
DOI: 10.1088/1367-2630/accb05
|View full text |Cite
|
Sign up to set email alerts
|

Floquet engineering with quantum optimal control theory

Abstract: Floquet engineering consists in the modification of physical systems by the application of periodic time-dependent perturbations. The search for the shape of the periodic perturbation that best modifies the properties of a system in order to achieve some predefined metastable target behavior can be formulated as an optimal control problem. We discuss several ways to formulate and solve this problem. We present, as examples, some applications in the context of material science, although the methods discussed he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…We have also shown that the Floquet topological phase can be directly linked to the well-established description of valence bond theory. There is an increasing effort to develop a molecular-level understanding of topological materials from the perspective of chemistry, which would open up the field for exploration with a more intuitive viewpoint based on the arrangement of atoms. Having established the connection between the Floquet topological phase in the Thouless pump and the valence bond description, an important question now is to what extent this topological phenomenon can be controlled rationally in terms of chemical understanding.…”
mentioning
confidence: 99%
“…We have also shown that the Floquet topological phase can be directly linked to the well-established description of valence bond theory. There is an increasing effort to develop a molecular-level understanding of topological materials from the perspective of chemistry, which would open up the field for exploration with a more intuitive viewpoint based on the arrangement of atoms. Having established the connection between the Floquet topological phase in the Thouless pump and the valence bond description, an important question now is to what extent this topological phenomenon can be controlled rationally in terms of chemical understanding.…”
mentioning
confidence: 99%